Gap and Inequality in the Economic Income of Independent Workers in the Region of Puno-Peru and the Effect of the Pandemic, 2019–2020 - Quispe Mamani, Julio C.; Flores Turpo, Giovana A.; Calcina Álvarez, Dominga A.; Yapuchura Saico, Cristóbal R.; Velásquez Velásquez, Wily L.; Aguilar Pinto, Santotomas L.; Quispe Quispe, Betsy; Quispe Maquera, Nelly B.; Cutipa Quilca, Balbina E. (Frontiers in Sociology, 2022)
Objective This article seeks to determine the social determinants of inequality in economic income in independent workers in the Puno region in the periods 2019 and 2020. Method The quantitative approach was used, with a descriptive and correlational design, considering the model of multiple regression. Result It was determined that there is a very important income gap by educational level due to the productive differential that COVID-19 affected all households; There is inequality in the economic income of independent workers, since in 2019 there was a greater inequality of economic income among independent workers (Gini=0.6142) in relation to the national level (Gini=0.415) and in 2020 inequality of income increased. economic income due to the COVID-19 problem, where the Gini coefficient rose to 0.7136 in relation to the national level (Gini=0.431). Conclusions The determining factors of the economic income of the independent worker in the Puno Region for the years 2019 and 2020 are the age of the worker, the level of education and the sex of the worker.